F118. EFFECT OF ARIPIPRAZOLE ONCE MONTHLY ON PERSONAL AND SOCIAL FUNCTIONING OF PATIENTS WITH SCHIZOPHRENIA: POST-HOC ANALYSES OF ACUTE AND LONG-TERM MAINTENANCE STUDIES. (9th April 2019) - Baker, Ross; Such, Pedro; Zhao, Cathy; Madera, Jessica
Abstract: Background: Along with control of psychotic symptoms, improved functioning is an important treatment goal in schizophrenia, particularly from the patient perspective. Efficacy of aripiprazole once-monthly 400 mg (AOM 400) in the treatment of acute exacerbation of schizophrenia was demonstrated in a randomized, placebo-controlled study (Study 291, NCT01663532), in which AOM 400 significantly improved clinical symptoms and social functioning. In two randomized, controlled trials of AOM 400 as maintenance treatment in stable patients with schizophrenia, AOM 400 delayed time to, and reduced the rate of, impending relapse vs placebo or a subtherapeutic dose of AOM. In both of these relapse prevention studies, as well as a long-term, open-label extension study (Study 248; NCT00731549), stability in clinical symptoms and patient functioning was maintained with long-term AOM 400 treatment. Here we report post-hoc analyses of the effect of AOM 400 on personal and social functioning from the acute setting and open-label extension studies. Methods: Post-hoc analyses were conducted on data from Study 291, a 12-week, randomized, double-blind, placebo-controlled trial of AOM 400 in patients experiencing an acute psychotic episode, and Study 248, a 52-week open-label extension of two randomized, controlled trials of AOM 400 as maintenance therapy. Assessment of functioning was made using the Personal and Social Performance (PSP) scale. For Study 291, results were also stratified by age (≤35 years or >35 years), and within-group difference in least squares mean (LSM) change from baseline for AOM 400 vs placebo was calculated in the efficacy sample to determine treatment effect using mixed-model repeated measures and analysis of covariance of observed case data. For Study 248, mean changes from baseline in PSP total score and across 4 domain subscales were tabulated by visit for the open-label AOM 400 maintenance phase and analyzed among observed cases in the efficacy sample. Results: In Study 291, 340 patients were included in the analysis (AOM 400, n=168 [n=49 aged ≤35 years, n=119 aged >35 years]; placebo, n=172 [n=54 aged ≤35 years, n=118 aged >35 years]). LSM (SE) change from baseline in PSP total score was significantly greater with AOM 400 compared with placebo at week 12 (13.0 [1.2] vs 5.5 [1.2], respectively; P<0.001). Treatment effects in patients ≤35 years of age were larger (11.1 [95% CI, 4.8 to 17.5]; P=0.001) than those in patients >35 years of age (3.6 [95% CI, –0.6 to 7.9]; P=0.09). In Study 248, 1, 081 patients entered the open-label maintenance phase and 858 completed the study. Mean (SD) PSP total score increased from 67.81 (11.79) at baseline to 68.62 (12.97) at the last study visit (week 52). Mean PSP domain scores at baseline were less than 2, indicating no greater than mild impairment. AOM 400 resulted in either small decreases or slight increases in scores for all PSP domain subscales, indicating maintenance of function over the course of the 52-week study. Discussion: Results from two post-hoc analyses of data from studies in both the acute treatment and maintenance settings demonstrate the efficacy of AOM 400 in improving and maintaining personal and social functioning in patients with schizophrenia. In the acute setting, improvements in functioning were observed across age groups (≤35 years, >35 years). Notably, the magnitude of functional improvement was largest in patients aged ≤35 years on AOM 400 and smallest in patients aged ≤35 years on placebo, findings that suggest a greater sensitivity to improvements in social functioning in younger patients with schizophrenia treated with AOM 400. The results of the long-term study support the use of a long-acting injectable antipsychotic to preserve functioning in patients with schizophrenia.